Food, Land, and Water (FLW) policies and institutions in Lao PDR - Inphonephong, Souphalack; Dubois, Mark; Kotchofa, Pacem (International Water Management Institute, 2025)
The Flagship Report on Food, Land and Water (FLW) Policies and Institutions in Lao PDR examines the governance and policy coherence of FLW systems in Lao PDR. The report was conducted from late 2023 to 2024 through i) a comprehensive desk review of national policies, legal frameworks, ministerial reports, and international assessments, and ii) key informant interviews with 24 policymakers, government officials, researchers, and representatives from international organisations and farmer organisations. The coherence assessment was based on policy designs and implementation impacts across five thematic areas, including food security and nutrition; poverty reduction and livelihood; gender, youth, and social inclusion; climate adaptation and resilience; and environmental health and biodiversity. Findings were classified through normative, horizontal, and vertical coherence as follows: